Affordances and constraints of synchronous and asynchronous computer-mediated collaborative writing formats in doctoral writing groups: A comparative literature review (Journal of Applied Learning and Teaching, 2026)
This conceptually informed narrative literature review, guided by affordance theory and the Community of Inquiry framework, examines the affordances and constraints of synchronous and asynchronous formats within doctoral writing groups, comparing how each format supports or challenges collaborative writing. The review finds that synchronous interactions can enhance collaboration by providing immediate feedback and fostering a strong sense of community, while also noting the potential scheduling difficulties associated with real-time engagement. Conversely, asynchronous interactions enable more thoughtful reflection and allow for greater reflexivity, though they may lack the immediacy and interpersonal connection of synchronous sessions. By analysing these dimensions, the review illuminates how each format shapes the dynamics of collaborative learning, reflective practice, and knowledge construction within doctoral writing groups. Drawing on a model of instructional design, this paper extends existing discussion on how digital technologies shape collaboration, knowledge construction, and academic writing development in doctoral education. Furthermore, it highlights how these writing groups function as knowledge-building communities where doctoral students do not merely exchange drafts but actively co-construct ideas through iterative discussion and feedback. Ultimately, it suggests that a hybrid approach that combines the immediacy and social connection of synchronous interactions with the flexibility and reflective depth of asynchronous methods may provide the most balanced and effective support for doctoral students’ writing development.